The Relevance of Religious Commodification in Ecranization of Films to the Internalization of Islamic Education in Higher Education - Hakim, Lukman; Puspita, Ayunda Riska; Bin Haji Abdullah, Luqman (IAIN Ponorogo, 2024)
This research examines factual issues, religious values, and forms of religious commodification in religious films into films and its relevance to internalizing Islamic education in higher education. Issues related to this topic are essential because the influence of movies is significant on students' character. Internalizing religious values in students requires effective media. One of them is film. This research employed a qualitative descriptive approach. This study analyzed the movie as a learning media. There are three results obtained in this study. First, factual issues of religious issues are used by film producers to gain economic benefits. Second, the religious values in the film can attract the public's attention to religious films. It is a form of commodification of religion in producing films. Third, there is a relevance between religious films and the internalization of Islamic education in higher education.